2014
DOI: 10.1063/1.4898001
|View full text |Cite
|
Sign up to set email alerts
|

Selective engineering of cavity resonance for frequency matching in optical parametric processes

Abstract: We propose to selectively engineer a single cavity resonance to achieve frequency matching for optical parametric processes in high-Q microresonators. For this purpose, we demonstrate an approach, selective mode splitting (SMS), to precisely shift a targeted cavity resonance, while leaving other cavity modes intact. We apply SMS to achieve efficient parametric generation via four-wave mixing in high-Q silicon microresonators. The proposed approach is of great potential for broad applications in integrated nonl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…The use of coupled microresonators for improving the phase matching conditions for efficient four‐wave mixing and parametric oscillation has been analyzed and demonstrated . The introduction of periodic perturbations to a waveguide, thus creating coupling between contra‐directional modes, has also been demonstrated for this purpose . With respect to microcomb generation, the possibility of reducing the pump threshold with the aid of coupled microresonators has been studied via simulation .…”
mentioning
confidence: 99%
“…The use of coupled microresonators for improving the phase matching conditions for efficient four‐wave mixing and parametric oscillation has been analyzed and demonstrated . The introduction of periodic perturbations to a waveguide, thus creating coupling between contra‐directional modes, has also been demonstrated for this purpose . With respect to microcomb generation, the possibility of reducing the pump threshold with the aid of coupled microresonators has been studied via simulation .…”
mentioning
confidence: 99%
“…Obviously, they can no longer be regarded as a superposition of two independent circulating modes with spin +½ and spin −½ around the cavity boundary. Their appearance is essentially due to the inevitable reduced geometric symmetry of the closed TI cavity boundary loop (see the theoretical deduction in Supplementary Note I), also observed in non-TI systems [ 52 , 53 ], and the final form of their presentation is indeed spilt SWMs [ 45–48 ], which have been systematically studied in optical microcavities, especially for sensing. When the TI cavity operates at these nondegenerate frequencies, the cavity should be treated as a whole instead of a closed loop, supporting only the collective resonance of the standing wave throughout its region.…”
Section: Resultsmentioning
confidence: 99%
“…This enables the periodic structure to operate as a homogeneous material [58][59][60] in which the frequency-wavevector curve is much less dispersive than those near the band edge. Despite the fact that photonic bandgap effects from this periodic structure do not spoil the predicted dispersion and the overall validity of the proposed design, previous studies 61,62 have indicated that splitting of some resonant peaks can be observed under a certain grating phase condition. However, this high-order grating effect is much slighter than the first one and is not included in our discussion.…”
Section: Comb Bandwidth Of Silicon Step-index Waveguidementioning
confidence: 85%